World drug report 2021 (United Nations)
As in previous reports, the 2021 World Drug Report (WDR) aims to improve the understanding of the world’s drug problem and to contribute towards fostering greater international cooperation for countering its impact on health, governance and security. Also, to the extent possible, the WDR contributes to the monitoring and reporting of SDGs. This edition includes an updated overview of recent trends on production, trafficking and consumption for non-medical purposes of key controlled substances. It further maintains a global overview of the baseline data and estimates on drug demand and supply and provides an analysis of the market for the different drugs